2014
DOI: 10.1590/s1806-66902014000200002
|View full text |Cite
|
Sign up to set email alerts
|

Production and nutritive value of ryegrass (cv. Barjumbo) under nitrogen fertilization

Abstract: ) and three replicates. Each plot measured 5x5 m, with 20 cm row spacing and 2.5 cm between plants, totaling 20 kg ha -1 of viable seeds. It was determined the dry matter production, crude protein level, total accumulation of crude protein and neutral detergent fiber, during the whole growth cycle of ryegrass in two crop seasons. Nitrogen fertilization promotes a significant and linear increase in dry matter yield and in accumulation of crude protein, with the best results with the highest rate evaluated (120 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 15 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…The study provided 13500 kg ha -1 of high-quality forage, with an average of 24% crude protein and 22% ADF over two years. Pavinato et al (2014) found the highest dry matter and crude protein yield with a dosage of 120 kg ha -1 of N in Brazil. Ozdemir et al (2019) reported that 500 kg ha -1 of nitrogen was ideal for high yield and high quality annual forage yields.…”
Section: Introductionmentioning
confidence: 92%
“…The study provided 13500 kg ha -1 of high-quality forage, with an average of 24% crude protein and 22% ADF over two years. Pavinato et al (2014) found the highest dry matter and crude protein yield with a dosage of 120 kg ha -1 of N in Brazil. Ozdemir et al (2019) reported that 500 kg ha -1 of nitrogen was ideal for high yield and high quality annual forage yields.…”
Section: Introductionmentioning
confidence: 92%
“…It was determined that increasing the nitrogen fertilizer doses increased chlorophyll content of Italian ryegrass [8]. In addition, the highest crude protein and DM yield in Italian ryegrass were obtained from 120 kg hada -1 nitrogen treatment [9]. Many researchers reported that the plant yield and quality improved with the increasing nitrogen doses in Italian ryegrass cultivation.…”
Section: Introductionmentioning
confidence: 99%
“…Although the high amount of N in the pasture (N200) did not result in a high accumulation rate, the numerical difference observed was enough to significantly influence the FM values. This biomass increase is explained by plant growth acceleration under N fertilization, which includes more tillering and leaf production improving the CP content of the pasture (Pavinato et al ., 2014; Restelatto et al ., 2014; Venturini et al ., 2017). In grasses, the additional N increases pasture nutritional value, especially its CP content, because the plant absorbs N in the form of ammonia, combines it with sugars and generates amino acids to form proteins (Andrews et al ., 2013).…”
Section: Discussionmentioning
confidence: 99%